PENGARUH PENAMBAHAN ND PADA PEMBENTUKAN FASE BI-2212 : (Bi1.63Pb0.37) Sr1.6Ca2.25Cu3.15Oy + Ndx - Suardana, P.; Putra Adnyana, I G A.; Sumadiyasa, M. (BULETIN FISIKA; Vol 13 No 2 (2012): BULETIN FISIKA)
Has conducted research related to the addition of Nd on formation 2212 phase of superconductor system BPSCCO : (Bi 1.63 Pb 0.37 ) Sr 1.6 Ca 2.25 Cu 3.15 O y + Nd x . The samples prepared by solid state reaction method with sintering temperature of 830 o C for 27 hours. XRD measurements revealed that the samples have shown the formation (Bi, Pb)-2212 phase with a good crystalinity (FWHM < 0.25 0 ). Provided that the volume fraction of (Bi, Pb)-2212 phase formed increases with increasing of addition of Nd. The highest volume fraction of 94.11% was obtained on the sample with the fraction of x = 0.050. The measurements of resistivity as a function of temperature with 4-point electrode method revealed that the samples have not shown the Tc o , but it have shown Tc on-set ~ 81K. The addition of Nd does not have a significant influence on the Tc on-set .